Architekturen des Geheimnisses - Horstmann, Mathias (Brill, 2024)
Hiding places are the last tiny blank spaces on the maps of a world disenchanted by science and enlightenment. With them, for the first time, a strange phenomenon is brought up that, due to its secret nature, just does not appear. They are a popular motif in the worlds of film, literature and in the press, but are ignored by the sciences.